Transoral incisionless fundoplication for patients with gastroesophageal reflux disease after peroral endoscopic myotomy: Prospective cohort - de Moura, Eduardo Guimarães Hourneaux; de Carvalho, Matheus Ferreira; Lira de Oliveira, Victor; Boghossian, Mateus Bond; Miranda Neto, Antonio Afonso; de Moura, Eduardo Turiani Hourneaux; Ardengh, André Orsini; Nasi, Ary; Chang, Kenneth; Funari, Mateus Pereira (Endoscopy International Open, 2025)
Achalasia is a condition related to failure of relaxation of the lower esophageal sphincter (LES). Treatment is based on reducing LES pressure. Although treatment is traditionally surgical, poor candidates for this modality may be treated with peroral endoscopic myotomy (POEM). However, POEM is associated with a relatively high incidence of gastroesophageal reflux disease (GERD). For cases refractory to proton pump inhibitors (PPIs), transoral incisionless fundoplication (TIF) is one of the endoscopic therapies proposed.This was a pilot single-center prospective cohort study including 10 patients with post-POEM GERD refractory to clinical management who underwent endoscopic treatment with the TIF procedure between February and November 2021. We included patients ≥ 18 years old who developed GERD after POEM.Technical success was achieved in all 10 cases treated with TIF. In 6- and 12-month follow-up, seven patients (70%) reduced PPI use. Two patients (20%) had no esophagitis initially, increasing to five (55%) at 6 months and four (44%) at 12 months. Symptom evaluation and GERD-HRQL questionnaire showed a significant score reduction at 6 months and a downward trend at 12 months. Mean Eckardt score showed a decreasing trend, although mean dysphagia score showed a slight tendency to increase in 1 year. The procedure was considered safe, with no adverse events.Use of TIF seems to be a feasible alternative for treating GERD after POEM, improving both clinical and endoscopic parameters and pHmetry in a considerable percentage of cases.
Keywords: Endoscopy Upper GI Tract; Reflux disease; Motility / achalasia; POEM